2017
DOI: 10.1073/pnas.1713328114
|View full text |Cite
|
Sign up to set email alerts
|

Closed-loop control of targeted ultrasound drug delivery across the blood–brain/tumor barriers in a rat glioma model

Abstract: Cavitation-facilitated microbubble-mediated focused ultrasound therapy is a promising method of drug delivery across the blood-brain barrier (BBB) for treating many neurological disorders. Unlike ultrasound thermal therapies, during which magnetic resonance thermometry can serve as a reliable treatment control modality, real-time control of modulated BBB disruption with undetectable vascular damage remains a challenge. Here a closedloop cavitation controlling paradigm that sustains stable cavitation while supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
183
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(188 citation statements)
references
References 55 publications
(64 reference statements)
5
183
0
Order By: Relevance
“…Non-linear acoustic emissions generated by the driven microbubbles are routinely monitored for assessment of therapeutic bioeffect. This is particularly the case for applications in which avoidance of overtreatment is critical, such as transcranial bloodÀbrain barrier disruption, for which recent clinical (Lipsman et al 2018) and extensive preclinical (Jones et al 2018;O'Reilly and Hynynen 2012;Sun et al 2017;Wu et al 2014) development is underway. With typical focused ultrasound fundamental driving frequencies (f 0 ) of several hundreds of kilohertz employed, for sufficient transmission across the skull, various combinations of harmonic emissions at nf 0 (where n is any integer), subharmonics at nf 0/2 and broadband emissions are commonly reported.…”
Section: Introductionmentioning
confidence: 99%
“…Non-linear acoustic emissions generated by the driven microbubbles are routinely monitored for assessment of therapeutic bioeffect. This is particularly the case for applications in which avoidance of overtreatment is critical, such as transcranial bloodÀbrain barrier disruption, for which recent clinical (Lipsman et al 2018) and extensive preclinical (Jones et al 2018;O'Reilly and Hynynen 2012;Sun et al 2017;Wu et al 2014) development is underway. With typical focused ultrasound fundamental driving frequencies (f 0 ) of several hundreds of kilohertz employed, for sufficient transmission across the skull, various combinations of harmonic emissions at nf 0 (where n is any integer), subharmonics at nf 0/2 and broadband emissions are commonly reported.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we plan to use pulse inversion in the short therapeutic pulses, to be able to detect weak cavitation emissions through the thick human skull (Pouliopoulos et al 2018). Future efforts will finally focus on using short pulses and PAM in closedloop (Sun et al 2017;Jones et al 2018;Kamimura et al 2018;Patel et al 2019) to improve the spatiotemporal control of acoustic cavitation activity within the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Focused ultrasound (FUS) serves as a non-invasive and non-ionizing therapeutic modality, with applications in lithotripsy (Miller and Thomas 1996), tumor ablation (Xia et al 2012), neuromodulation (Kamimura et al 2016;Tyler et al 2018) and essential tremor treatment (Lipsman et al 2013;Elias et al 2016). Microbubbles are routinely used as contrast agents in ultrasound imaging (Cosgrove and Harvey 2009) and as stress mediators in ultrasound therapy (Coussios and Roy 2008) to deliver drugs into cells Shamout et al 2015), tumors (Graham et al 2014;Sun et al 2017;Arvanitis et al 2018) or tissues (Kotopoulis et al 2013). In conjunction with systemically circulating microbubbles, FUS can perform targeted, noninvasive and reversible bloodÀbrain barrier (BBB) opening (Hynynen et al 2001;Konofagou 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon has been studied for more than a decade. Both small and large animal studies have shown it is safe, and the ability to monitor the behavior of the MBs via their acoustic emissions has proven instrumental in controlling the BBB opening and even subsequent drug delivery . Such approaches have also been used to successfully deliver neurotrophic factors and genes to the brains of rodents .…”
mentioning
confidence: 99%
“…Both small and large animal studies have shown it is safe, and the ability to monitor the behavior of the MBs via their acoustic emissions has proven instrumental in controlling the BBB opening [14][15][16][17] and even subsequent drug delivery. 18 Such approaches have also been used to successfully deliver neurotrophic factors and genes to the brains of rodents. [19][20][21] Importantly, the BBB opening with MBs and ultrasound has entered clinical trials for patients with Alzheimer's disease and primary brain tumors [22][23][24] and shows an excellent safety profile thus far.…”
mentioning
confidence: 99%